2018
DOI: 10.2355/isijinternational.isijint-2017-306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Process Conditions on Angular Distortion Induced by Bead-on-plate Welding

Abstract: In this study, the effect of welding process and heat input conditions on the angular distortion induced by bead-on-plate welding was investigated through a numerical approach. Numerical models of gas metal arc welding (GMAW) and gas tungsten arc welding (GTAW), which were developed in a previous study, were utilized for accurate distortion analyses. The calculated relation between welding conditions and angular distortion was quantified by using the conventional heat input parameter derived from welding therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…This study only examines transverse angular distortion because it is easily identifiable and quantifiable. Previous studies [5,6,8,9] have reported that subthreshold angular distortion was proportional to heat input and inversely proportional to the square of thickness. Herein, we define this relationship as a heat input parameter, representing electric energy divided by traveling speed, to evaluate angular distortion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study only examines transverse angular distortion because it is easily identifiable and quantifiable. Previous studies [5,6,8,9] have reported that subthreshold angular distortion was proportional to heat input and inversely proportional to the square of thickness. Herein, we define this relationship as a heat input parameter, representing electric energy divided by traveling speed, to evaluate angular distortion.…”
Section: Methodsmentioning
confidence: 99%
“…Luo et al [7] proposed a mechanism for generating welding distortion by inherent strain (ε * = −ε Y /β = −σ Y /βE) and yielding temperature (T 1 = σ Y /βEα) at which stress just reached yield stress during heating. Mochizuki and Okano [8,9] proposed the parameter (b m /h)/(d m /h) as a mechanical melting zone, which was more accurate than the heat input parameter presented by Satoh and Terasaki [6], by considering heat-affected-zone width and height. Its usefulness was verified through analyses of various BOP welding processes; the subthreshold parameter demonstrated that reinforcement of the bead negligibly affected angular distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold seems to occur as the center position of the contracted load becomes closer to the neutral axis. The data above the threshold produce low measurement accuracy of angular distortion due to in-plane shrinkage, and they exhibit nonlinearity [2,3]. If the center position of the shrinkage load agrees with the neutral axis, the angular distortion becomes zero, and shrinkage reaches its maximum.…”
Section: Bead-on-plate Welding Experimentsmentioning
confidence: 99%
“…Many researchers verified this relationship afterwards, being widely applied across industries. Mochizuki and Okano [3] recently found that this relationship differs, depending on the welding process, and that the factor that actually affects angular distortion is the mechanical melting region, whose temperature corresponds to that at which the stiffness of the material sharply decreases. Through finite element analysis, they also found that angular distortion is proportional to the width and depth of the region and inversely proportional to the square of thickness, and then confirmed the applicability of these relationships to various types of welding processes.…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed the behavior of angular distortion along the passes performed. Mochizuki and Okano investigated the effect of the welding process and heat input conditions on the angular distortion induced by bead-on-plate welding through a numerical approach [21]. They developed the parameter of mechanical melting region on the plate thickness and found that it was the dominant factor for accurately quantifying angular distortions.…”
Section: Introductionmentioning
confidence: 99%